Natural additive (nopal mucilage) on the electrochemical properties of concrete reinforcing steel - Díaz Blanco, Yohandry; Menchaca Campos, Elsa Carmina; Rocabruno Valdés, Carolin Ivette; Uruchurtu Chavarín, Jorge (Revista ALCONPAT, 2019)
In this investigation the effect of Nopal mucilage on the electrochemical properties of concrete was evaluated. Three concentrations of this additive were designed with a Nopal-water ratio of 1:1, 1:2 and 1:3. Compressive tests were performed after 28 days of curing. Specimens were evaluated for 270 days through various electrochemical techniques such as: Open Circuit Potential (OCP), Electrochemical Noise (EN) and Linear Polarization Resistance (LPR). Results indicate a decrease in compressive resistance in samples with Nopal mucilage at 28 days. The onset of steel corrosion was delayed and the corrosion rate was lower for samples with Nopal mucilage. The conservation and storage of this additive before being used in concrete can be a challenge to analyze.